Feeding Tall Fescue Seed during Mid and Late Gestation Influences Subsequent Postnatal Growth, Puberty, and Carcass Quality of Offspring - Maslyn A. Greene; Jessica L. Britt; J. Keith Bertrand; James L. Klotz; William Bridges; John G. Andrae; Susan K. Duckett (Animals, 2020)
Weaned lambs (n = 82), born to ewes fed endophyte-free (E−) or endophyte-infected (E+; 1.77 mg hd−1 d−1 ergovaline + ergovalinine) tall fescue seed from d 35 to 85 of gestation (MID) and/or d 86 of gestation to parturition (LATE), were used to examine how ergot alkaloid exposure during fetal development altered subsequent puberty attainment or carcass quality. Lambs were weaned at 75 d of age and separated by sex to assess puberty in ewe lambs (n = 39) and to evaluate growth, carcass and meat quality in wethers (n = 43). Data were analyzed with maternal fescue treatment, stage of gestation, and two-way interaction in the model. Age at puberty tended (P = 0.06) to be longer for ewe lambs born to dams fed E+ fescue during LATE gestation versus those fed E−. Post-weaning average daily gain tended to be higher (P = 0.07) for wether lambs born to dams fed E+ fescue seed during MID gestation compared to E−. Exposure to ergot alkaloids during fetal growth altered (P < 0.10) longissimus muscle weight and color, lipid deposition, fatty acid composition, and shear force values of semimembranosus muscle in wether lambs. These results indicate that exposure to ergot alkaloids in utero does alter subsequent post-weaning puberty attainment and body composition in offspring.